Post‐acquisition analysis of untargeted accurate mass quadrupole time‐of‐flight MSE data for multiple collision‐induced neutral losses and fragment ions of glutathione conjugates. (30th December 2014) - Brink, Andreas; Fontaine, Fabien; Marschmann, Michaela; Steinhuber, Bernd; Cece, Esra Nurten; Zamora, Ismael; Pähler, Axel
<x xml:space="preserve">Abstract</x> RATIONALE Analytical methods to assess glutathione (GSH) conjugate formation based on mass spectrometry usually take advantage of the specific fragmentation behavior of the glutathione moiety. However, most methods used for GSH adduct screening monitor only one specific neutral loss or one fragment ion, even though the peptide moiety of GSH adducts shows a number of other specific neutral fragments and fragment ions which can be used for identification. METHODS Nine reference drugs well known to form GSH adducts were incubated with human liver microsomes. Mass spectrometric analysis was performed with a quadrupole time‐of‐flight mass spectrometer in untargeted accurate mass MSE mode. The data analysis and evaluation was achieved in an automated approach with software to extract and identify GSH conjugates based on the presence of multiple collision‐induced neutral losses and fragment ions specific for glutathione conjugates in the high‐energy MS spectra. RESULTS In total 42 GSH adducts were identified. Eight (18%) adducts did not show the neutral loss of 129 but were identified based on the appearance of other GSH‐specific neutral losses or fragment ions. In high‐energy MSE spectra the GSH‐specific fragment ions of m/z 308 and 179 as well as the neutral loss of 275 Da were complementary to the commonly used neutral loss of 129 Da. Further, one abundant (yet unpublished) GSH conjugate of troglitazone formed in human liver microsomes was found. CONCLUSIONS A software‐aided approach was developed to reliably retrieve GSH adduct formation data out of untargeted complex full scan QTOFMSE data in a fast and efficient way. The present approach to detect and analyze multiple collision‐induced neutral losses and fragment ions of glutathione conjugates in untargeted MSE data might be applicable to higher throughput to assess reactive metabolite formation in drug discovery. Copyright © 2014 John Wiley & Sons, Ltd.